Znaczenie wybranych dochodów podatkowych pobieranych przez organy podatkowe w województwie mazowieckim w dochodach budżetu państwa - Furman, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
This article discusses the issue of budgetary revenue obtained in the years 2012 - 2016 in the Mazowieckie Province with: personal income tax, corporate income tax, income tax on goods and services. Revenue accrued in the said administrative unit was charged to all revenue generated in the central budget. Finally, conclusions from the analysis have been presented, which indicate that the importance of tax revenue transferred directly from the tax authorities to the central budget is growing.
Keywords: tax; budget; participation; income taxes